Influence of setting angle of the airfoil cascade on the flow «choking» regimes in the blade channel - Терещенко, Юрий Матвеевич; Дорошенко, Екатерина Викторовна; Араш, Техрани (Eastern-European Journal of Enterprise Technologies, 2014)
The emergence of “choking” regimes of last stages leads to the stall in the blade rows of first stages, appearance of rotating stall and surge, and is one of the main causes of reduced GTE effectiveness on the off-design operating conditions. The paper deals with investigating the impact of setting angle in the airfoil cascade at the critical flow regime. To solve this problem, a series of gas-dynamic calculations for compressor airfoil cascade with different setting angles γ=30º, γ=40º, γ=50º, γ=60º, γ=70º was carried out. The computational domain for this problem consists of one blade and one blade channel. To solve this problem, irregular adaptive grid was selected. The turbulent gas flow calculation was performed by numerical solution of the averaged Navier-Stokes equations (Reynolds equations). To close the Navier-Stokes equations, the Menter's SST turbulence model was chosen. The second-order design scheme with the local use of the first-order design scheme was used for the calculation. Comparison of theoretical and experimental research results have shown that the flow nature in the blade channels and boundary layer formation depend strongly on the airfoil setting angle. With a decrease in the airfoil setting angle there is a significant decrease in the relative value of the minimum actual flow area of blade channels (described in aerodynamics as free area), which leads to a decrease in the Mach number value at the cascade entrance, at which the flow “choking” regime in blade channels by air flow occurs. These features should be taken into account in “choking” regime calculations. The obtained generalized characteristics of “choking” regimes of compressor cascades can be used in calculating “choking” regimes of the axial flow compressor stages and determining the boundaries of gas-dynamic stability of multistage axial flow compressors.